Can The Academic Quality And Service Of Northern Green School Medan Enhance Parents' Satisfaction and Loyality? - Anton; Pradiani, Theresia; Fathorrahman (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2025)
Parents’ satisfaction and loyalty towards their chosen school for their children’s education are vital for the sustainability and existence of private schools. This study aims to confirm the critical role of academic quality and service in increasing the satisfaction and loyalty of parents of students. Through a questionnaire survey of 30 parents of Northern Green School Medan students, using a saturated sampling technique, quantitative data were carefully analyzed using PLS analysis. The results of this study prove all hypotheses. Each relationship between variables has been empirically proven to be statistically significant and positively correlated. The partial mediation role of parental satisfaction on the influence of academic quality and service on their loyalty is proven accurate. This study is limited to a small sample, so generalization to all schools cannot be done. Further research is expected to expand the research subjects from several schools with the same level and conduct qualitative research through more in-depth interviews related to the academic quality and service expected by parents.